ANALYSIS OF THE INFLUENCE OF CUTTING MODES ON THE ACCURACY OF THE DIMENSIONS OF THE MACHINED BLANKETS DURING TURNING AND MILLING WITH ACCOUNTING FOR ELASTIC DEFORMATIONS OF ITS SURFACE - KUSHNIRCUK, ANDRIY; TKACHUK, VITALIY (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The quality of the resulting surface of elements manufactured by printing is a factor that determines their use in various areas, from prototyping to mass production, to eliminating workpiece defects, reducing surface roughness and adapting the shape of the part to technical requirements. However, the process uses several variables with a wide range of values, for example, the choice of turning tools, milling cutters including the material of the cutting inserts, the choice of cutting parameters and the determination of processing conditions. Conducting an analytical analysis of the influence of cutting modes of plastic parts after FDM printing, in connection with the emergence of new plastic materials, on the accuracy of the surfaces processed by turning and milling, taking into account elastic deformations of the workpiece surface, with the determination of technological parameters of the processes of turning and milling on CNC machines is an urgent task. The influence of cutting modes on the accuracy of the dimensions of the workpieces processed during turning and milling, taking into account elastic deformations of its surface, is considered. An analytical analysis of the influence of cutting modes during turning and milling of plastic blanks obtained after FDM printing on the accuracy of execution of critical surfaces was carried out. Diagrams of changes in cutting forces during turning and milling during finishing and roughing types of processing were constructed, from which the values ​​of elastic deformations of the processed surfaces were determined. To verify the obtained results, a part of a complex shape “Improvement” was manufactured using the FDM printing method and the connecting surfaces were processed using mechanical cutting (turning, milling), for which the accuracy after printing was insufficient, which was revealed by measuring the corresponding surfaces. After mechanical processing of the corresponding surfaces, the obtained dimensional accuracy was measured. The measurement results showed a slight discrepancy between the obtained geometric parameters, but they are within the tolerance limits for the corresponding dimensions.
Keywords: cutting modes; elastic deformations of the surface; dimensional accuracy; turning; milling